Tailoring the Aqueous Synthesis and Deposition of Copper Nanowires for Transparent Electrodes and Heaters. Issue 20 (10th August 2017) - Bobinger, Marco; Mock, Josef; La Torraca, Paolo; Becherer, Markus; Lugli, Paolo; Larcher, Luca
Abstract: Due to the high abundance of copper on the earth and its high intrinsic electrical conductivity, copper nanowires (CuNWs) represent a promising material for transparent electrodes. In this work, an environmentally friendly and scalable synthesis that requires a low process temperature is studied. The optimum temperature is found at 79 °C, which results in nanowires with the lowest diameters. The as‐synthesized solution is sprayed to transparent conducting films, which are in turn subjected to various post‐treatments such as thermal sintering or washing with propionic acid to enhance their electro‐optical performance. Following both the optimum protocol for the synthesis and post‐treatment, a sheet resistance of 10.3 Ω ◻ −1 at a transparency of 83.4% is achieved. Moreover, the CuNW‐films are tested as transparent heaters and show a homogeneous heat distribution. For the electrical properties of the films, a temperature dependence of resistance that is lowered around 28% compared to the one for bulk copper is found. Abstract : The tailoring of an environmentally friendly and scalable solution‐based synthesis for copper nanowires is presented. Via a facile spray process, transparent conducting films are fabricated and subjected to different postdeposition treatments to lower their sheet resistances. Moreover, the films are characterized as transparent heaters that can be continuously operated for more than six days.